Reflecting on hard and soft coups: a comparison of Aquarius by Kleber Mendonça Filho and Land in Anguish by Glauber Rocha - Carolin Overhoff Ferreira (Brasiliana: Journal for Brazilian Studies, 2018)
This article aims to study the film Aquarius (2015) by Kleber Mendonça Filho in comparison with Land in Anguish (1967) by Glauber Rocha. The interest in analyzing both films stems from the polemical reception that Aquarius received after its director and cast used the international launch at the Cannes Film Festival in 2016 to protest publically against the impeachment of Brazilian president Dilma Rousseff, denounced by them as a soft coup. Land in Anguish, on the other hand, has long been considered an allegory of Brazil’s political situation after the military coup in 1964. This article will ask if any of the two films can be read as a diagnosis of the country and if how. To do so this study will be guided by the anthropological definition of film developed by German philosopher Martin Seel (2013) who understands the media as the art form that most strongly is capable of moving us, as much emotionally as intellectually, and, in consequence, make us move. I will therefore discuss both Aquarius and Land in Anguish’s potentials to move us and to make us move, asking if they can make us feel and understand Brazil so as to make us act – perchance – within its socio-political structure.